2001
DOI: 10.1002/neu.1011
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation reveals regulation of ciliary activity by serotonergic neurons in molluscan embryos

Abstract: Early in embryonic development, the pond snail Helisoma trivolvis exhibits a rotational behavior that is generated by beating of cilia in the dorsolateral and pedal bands. Although previous anatomical and pharmacological studies provided indirect evidence that a pair of serotonergic neurons, Embryonic Neurons C1 (ENC1s), is involved in regulating embryonic rotation, direct evidence linking ENC1 to ciliary function is still lacking. In the present study, we used laser microbeams to perturb ENC1 in vivo while mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 54 publications
5
57
1
Order By: Relevance
“…Perhaps the prominent surges revealed in the analysis of rotational dynamics (Fig.2A) are dopamine-induced events associated with bursts of activity in the TAC neurons. These data are consistent with the TAC neurons of L. stagnalis functioning very similarly to their ENC1 homologs in H. trivolvis (Kuang and Goldberg, 2001), despite having a different primary neurotransmitter.…”
Section: Pharmacological Analysis Of the Hypoxia Responsesupporting
confidence: 87%
See 4 more Smart Citations
“…Perhaps the prominent surges revealed in the analysis of rotational dynamics (Fig.2A) are dopamine-induced events associated with bursts of activity in the TAC neurons. These data are consistent with the TAC neurons of L. stagnalis functioning very similarly to their ENC1 homologs in H. trivolvis (Kuang and Goldberg, 2001), despite having a different primary neurotransmitter.…”
Section: Pharmacological Analysis Of the Hypoxia Responsesupporting
confidence: 87%
“…Acetylated tubulin immunofluorescence revealed that L. stagnalis embryos contained the same ciliated structures on the embryonic surface as those previously described in H. trivolvis (Kuang and Goldberg, 2001;Doran et al, 2004), including two dorsolateral bands of cilia, a pedal band of cilia, the dorsal stomodeum and scattered single ciliary cells (Fig.1). Lymnaea stagnalis embryos also contained the ciliated apical plate (Fig.1), which is absent in H. trivolvis.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations